Corynoxine Protects Dopaminergic Neurons Through Inducing Autophagy and Diminishing Neuroinflammation in Rotenone-Induced Animal Models of Parkinson’s Disease - Chen, Leilei; Huang, Yujv; Yu, Xing; Lu, Jiahong; Jia, Wenting; Song, Juxian; Liu, Liangfeng; Wang, Youcui; Huang, Yingyu; Xie, Junxia; Li, Min (Frontiers in Pharmacology, 2021)
Recent studies have shown that impairment of autophagy is related to the pathogenesis of Parkinson’s disease (PD), and small molecular autophagy enhancers are suggested to be potential drug candidates against PD. Previous studies identified corynoxine (Cory), an oxindole alkaloids isolated from the Chinese herbal medicine Uncaria rhynchophylla (Miq.) Jacks, as a new autophagy enhancer that promoted the degradation of α-synuclein in a PD cell model. In this study, two different rotenone-induced animal models of PD, one involving the systemic administration of rotenone at a low dosage in mice, and the other involving the infusion of rotenone stereotaxically into the substantia nigra pars compacta (SNpc) of rats, were employed to evaluate the neuroprotective effects of Cory. Cory was shown to exhibit neuroprotective effects in the two rotenone-induced models of PD by improving motor dysfunction, preventing tyrosine hydroxylase (TH)-positive neuronal loss, decreasing α-synuclein aggregates through the mechanistic target of rapamycin (mTOR) pathway, and diminishing neuroinflammation. These results provide pre-clinical experimental evidence supporting the development of Cory into a potential delivery system for the treatment of PD.